PENDIDIKAN KARAKTER BERBASIS SEKOLAH: PERAN GURU, ORANG TUA, DAN EKSTRAKURIKULER DALAM MEMBENTUK AKHLAK MULIA DI MI AL–WASATIYAH TANGERANG - Avita Putri Dianti; Aulia Putri Velani; Arfikah Zahiroh; Rahmawati Eka Saputri (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The results of the study indicate that school-based character education at MI Al-Wasatiyah Tangerang runs effectively through the integration of the roles of teachers, parents, and extracurricular activities. . And also through observations and interviews, MI Al-Wasatiyah fosters moral values through daily habituation programs where children are required to read the Quran, pray dhuha and so on as well as to integrate values into the curriculum and teaching methods, and the importance of teachers as models and mentors. Parents and extracurricular activities contribute to implementation, but there is room for improvement in personal direction and parental participation. The quality of character education must be improved through training teachers, guidance engineering systems, digital tracking, and system management and providing effective communication strategies to parents for optimal results. This study concludes that MI Al-Wasatiyah has achieved a significant level of success in character education programs, with a note on the need to increase personal guidance for 20% of 40 students, namely 8 students who still need special attention, as well as the development of a digital tracking system for continuous monitoring of student progress. As for 80% of the 40 students, namely around 32 other students, they do not require special attention.